Penerapan Strategi Komunikasi Pemasaran untuk Meningkatkan Minat Beli terhadap Produk Kosmetik (Studi Kasus PT X). - Apsari, Novita; Siregar, Jenny Sista; Jubaedah, Lilis (Universitas Negeri Jakarta, 2025)
This study aims to identify and analyze the marketing communication strategy that implemented by PT X. The marketing communication strategy applied by PT X is a marketing strategy that collaborates with Makeup Artists to increase purchasing intention from target consumers. The method used in this study is a qualitative research method with data collection techniques through in-depth interviews. Researcher conducted interviews with six informants. The three informants interviewed were PT X's internal team, and the other three were people who worked as Makeup Artists who collaborated on the marketing strategy that implemented by PT X. The results of this study indicate that the marketing communication strategy of PT X in collaboration with Makeup Artist in the Makeup Academy Project is a marketing strategy that can increase the purchase intention from target consumers. In implementing this strategy, Makeup Artist is a sales agent who promotes PT X's cosmetic products to the targeted consumers, they are the students of the Project Makeup Academy. Keywords: Marketing Communication Strategy, Makeup Artist, Project Makeup Academy, Buying Interest.